2000
DOI: 10.1002/1521-4184(200012)333:12<431::aid-ardp431>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Novel Piperidinedione Analogs as Inhibitors of Breast Cancer Cell Growth

Abstract: We previously reported the utility of antineoplaston‐A10 (3‐phenylacetylamino‐2,6‐piperidinedione) as an endogenous cancer protector and immune modulator in breast cancer patients (Cancer Lett., 2000, 157, 57). In this study, four new piperidinedione A10 analogs were synthesized and tested for their antimitotic activity on a human breast cancer cell line against the prototype A10 and the antibreast cancer drug tamoxifen. Moreover, the DNA binding capacity of such compounds was evaluated against A10. (E)‐3‐(4‐N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Conversely, hydrolysis of the piperidinedione ring of A10 yields PAG. Early work indicated that A10 had reproducible but weak antineoplastic activity which encouraged us to design more active analogs [26][27][28]. Our design strategy was based upon observations that hormone antagonists fit at least partially within the same site in DNA as agonists [50].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Conversely, hydrolysis of the piperidinedione ring of A10 yields PAG. Early work indicated that A10 had reproducible but weak antineoplastic activity which encouraged us to design more active analogs [26][27][28]. Our design strategy was based upon observations that hormone antagonists fit at least partially within the same site in DNA as agonists [50].…”
Section: Discussionmentioning
confidence: 99%
“…The piperidinedione derivatives used in this study included 3-phenylacetylamino-2,6-piperidinedione (A10), phydroxy-A10 (p-OH A10), 3-(4-nitrocinnamoylamino)-2,6-piperidinedione (B3) [28], phenylacetylglutamine (PAG), phenylacetate (PA), and p-chlorophenylacetate (CPA) (Fig. 1).…”
Section: Cell Culture and Reagentsmentioning
confidence: 99%
See 3 more Smart Citations